Association of mental health status with perceived barriers to healthy diet among Bangladeshi adults: a quantile regression-based approach - Hasan, A. B. M. Nahid; Kundu, Satyajit; Jahan, Ishrat; Basak, Tapu; Hasan, Mahamudul; Sharif, Azaz Bin (Frontiers in Public Health, 2025)
IntroductionMaintaining a healthy diet is essential for both physical and mental well-being. This study investigated the association of mental health status with perceived barriers to maintaining healthy diets among Bangladeshi adults.MethodThis cross-sectional study was conducted between January to June 2023 in Bangladesh. A total of 400 adults aged between 18 and 60 years who reside in Dhaka, Chattogram, and Gazipur cities were recruited using a multistage sampling technique. A questionnaire consisting of 12 questions adapted from previous literature was used to assess barriers to healthy diets. Mental health status was measured using the validated DASS-21 scale. A quantile regression-based approach was used to ascertain the association between mental health status and barriers to healthy diets.ResultsThe five most frequently reported barriers to a healthy diet were the use of junk food as a reward or treat (56.25%), difficulty in controlling eating habits when with friends (56%), the cost of healthy food (44.5%), difficulty in taking healthy food at work (46.5%), and difficult to stay motivated to eat healthy food (25%). The study found that gender, marital status, living arrangement, working hours, and family monthly income were significantly associated with perceived barriers to healthy diets. Mental health status was observed to be associated with barriers to healthy diet scores. Depression (β =0.34, 95% CI: 0.17 to 0.51) and anxiety (β =0.14, 95% CI: 0.01 to 0.28) were significantly associated with perceived barrier scores at the 50th quantile. Stress was also significantly associated with perceived barrier scores at the 10th (β =0.18, 95% CI: 0.09 to 0.27) and the 25th quantiles (β =0.12, 95% CI: 0.03 to 0.21).ConclusionIn light of the findings, it is imperative to prioritize the advocacy of policies that integrate mental health services and stress management strategies into public health initiatives.